2013
DOI: 10.1103/physrevc.87.035803
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy collective excitations in the neutron star inner crust

Abstract: We study the low-energy collective excitations in the inner crust of the neutron star, where a neutron superfluid coexists with a Coulomb lattice of nuclei. The dispersion relation of the modes is calculated systematically from a microscopic theory including neutron band structure effects.These effects are shown to lead to a strong mixing between the Bogoliubov-Anderson bosons of the neutron superfluid and the longitudinal crystal lattice phonons. In addition, the speed of the transverse shear mode is greatly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 57 publications
4
112
0
Order By: Relevance
“…At ρ ≈ 10 12 − 10 14 g cm −3 the conductivity due to superfluid phonons was estimated to be significantly larger than that due to lattice phonons and comparable to electron conductivity when T ≈ 10 8 K. The authors found that this mode of heat conduction could limit the anisotropy of temperature distribution at the surface of highly magnetized neutron stars. However, new studies of the low-energy collective excitations in the inner crust of the neutron star (Chamel 2012;Chamel et al 2013), including neutron band structure effects, show that there is a strong mixing between the Bogoliubov-Anderson bosons of the neutron superfluid and the longitudinal crystal lattice phonons. In addition, the speed of the transverse shear mode is greatly re-duced as a large fraction of superfluid neutrons are entrained by nuclei.…”
Section: Superfluid Effects On Heat Conductionmentioning
confidence: 99%
“…At ρ ≈ 10 12 − 10 14 g cm −3 the conductivity due to superfluid phonons was estimated to be significantly larger than that due to lattice phonons and comparable to electron conductivity when T ≈ 10 8 K. The authors found that this mode of heat conduction could limit the anisotropy of temperature distribution at the surface of highly magnetized neutron stars. However, new studies of the low-energy collective excitations in the inner crust of the neutron star (Chamel 2012;Chamel et al 2013), including neutron band structure effects, show that there is a strong mixing between the Bogoliubov-Anderson bosons of the neutron superfluid and the longitudinal crystal lattice phonons. In addition, the speed of the transverse shear mode is greatly re-duced as a large fraction of superfluid neutrons are entrained by nuclei.…”
Section: Superfluid Effects On Heat Conductionmentioning
confidence: 99%
“…The former has amplitude around the surface region r ≈ 3 − 8 fm of the cluster while the latter does not penetrate into r < 7fm, hence the overlap integral could become small. This might lead to a SPH-LPH coupling weaker than that evaluated in macroscopic approaches [2,[5][6][7][8], where this effect is not taken into account.…”
Section: Dipole Superfluid Phonon Modementioning
confidence: 99%
“…Many of the previous studies of the SPH in the inner crust have been performed in the framework of the macroscopic effective theory or the hydrodynamical approaches [2,[5][6][7][8]. However, inhomogeneity of inner crust matter may affect the character of the SPH and the coupling to the lattice phonon, and therefore nuclear many-body approaches are required to provide microscopic information on SPH in the inner crust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the quasi-free neutrons are superfluid, assuming the traction vanishes at the crust-core boundary may also be a good approximation. An additional impact of the superfluid is that some fraction, f ent , of the quasi-free neutrons are entrained with the nuclei [36,37]. We assume zero traction at the crust-core transition and leave a more complete description of matter at the highest densities to future work.…”
Section: Torsional Oscillations In a Strong Magnetic Fieldmentioning
confidence: 99%